Update 7:35pm UTC 3/23/14: I've reposted this quesion on MathOverflow here.

As an assignment in my commutative algebra class, I need to prove the Mayer-Vietoris sequence for local cohomology:

Let $R$ be a Noetherian ring, $I,J$ $R$-ideals, and $M$ an $R$-module. Show that there is a long exact sequence $$ \cdots \rightarrow H^i_{I+J}(M)\rightarrow H^i_I(M)\oplus H^i_J(M) \rightarrow H^i_{I\cap J}(M) \rightarrow H^{i+1}_{I+J}(M)\rightarrow\cdots. $$

I've reduced this to proving the following:

Let $R$ be a Noetherian ring, $I,J$ $R$-ideals, and $M$ an $R$-module such that $\Gamma_{I\cap J}(M)=M$. Then $M=\Gamma_I(M)+\Gamma_J(M)$.

However, in trying to prove this, I ended up "proving" that $M/(\Gamma_I(M)+\Gamma_J(M))\cong (\Gamma_I(M)+\Gamma_J(M))/\Gamma_I(M)$, which is certainly false in general---if it were true, then (assuming we've shown $M=\Gamma_I(M)+\Gamma_J(M)$) setting $J=0$, we'd get $\Gamma_I(M)=M$ for every ideal $I$ and every $R$-module $M$, which is clearly false.

Question: Where did I go wrong?

Here's my "proof" of the incorrect "fact":

Consider the short exact sequence $$ 0 \to \frac{\Gamma_I(M)}{\Gamma_I(M)\cap \Gamma_J(M)} \to \frac{M}{\Gamma_J(M)}\to \frac{M}{\Gamma_I(M)+\Gamma_J(M)}\to 0.\tag{1}$$ Notice that if $x\in M$, so that $(I\cap J)^n x=0$ for some $x\geq 0$, then $I^n(J^n x)\subseteq (IJ)^nx\subseteq (I\cap J)^n x=0$; hence, $J^nx \subseteq \Gamma_I(M)\subseteq \Gamma_I(M)+\Gamma_J(M)$. Thus, $$ \Gamma_J\left(\frac{M}{\Gamma_I(M)+\Gamma_J(M)}\right) = \frac{M}{\Gamma_I(M)+\Gamma_J(M)} \tag{2},$$ and so (by a previous homework set) $$ H^i_J\left(\frac{M}{\Gamma_I(M)+\Gamma_J(M)}\right) = 0 \quad \text{for all}\quad i>0 \tag{3}.$$ Also by a previous homework set, $$ \Gamma_J\left(\frac{M}{\Gamma_J(M)}\right)=0. \tag{4}$$ Hence, applying the long exact sequence of $H_J$ to (1), and using (2), (3), and (4), we get an exact sequence $$0\to \frac{M}{\Gamma_I(M)+\Gamma_J(M)} \to H^1_J\left(\frac{\Gamma_I(M)}{\Gamma_I(M)\cap \Gamma_J(M)}\right) \to H^1_J\left(\frac{M}{\Gamma_J(M)}\right)\to 0. $$ Hence, $$ \frac{M}{\Gamma_I(M)+\Gamma_J(M)} \cong \ker \left[H^1_J\left(\frac{\Gamma_I(M)}{\Gamma_I(M)\cap \Gamma_J(M)}\right) \to H^1_J\left(\frac{M}{\Gamma_J(M)}\right)\right].\tag{5}$$

Now, since $\Gamma_I(M)\cap \Gamma_J(M)=\Gamma_J(\Gamma_I(M))$, we get $$ \frac{\Gamma_I(M)}{\Gamma_I(M)\cap \Gamma_J(M)} = \frac{\Gamma_I(M)}{\Gamma_J(\Gamma_I(M))}.$$ From a previous homework assignment, if $N$ is any $R$-module, $R$ is Noetherian, and $J$ is an $R$-ideal, then for $i>0$, the map $H^i(N)\to H^i(N/\Gamma_I(N))$ induced by the projection $N\to N/\Gamma_I(N)$ is an isomorphism. Therefore, (5) becomes $$ \frac{M}{\Gamma_I(M)+\Gamma_J(M)} \cong \ker \left[H^1_J(\Gamma_I(M)) \to H^1_J(M)\right],$$ where $H^1_J(\Gamma_I(M)) \to H^1_J(M)$ is the natural map. But by the long exact sequence of $H_J$, $$ \ker \left[H^1_J(\Gamma_I(M)) \to H^1_J(M)\right] \cong \frac{\Gamma_J(M)}{\Gamma_J(\Gamma_I(M))} \cong \frac{\Gamma_I(M)+\Gamma_J(M)}{\Gamma_I(M)}.$$ Thus, $$ \frac{M}{\Gamma_I(M)+\Gamma_J(M)} \cong \frac{\Gamma_I(M)+\Gamma_J(M)}{\Gamma_I(M)}.$$


1 Answer 1


I have posted an answer to the MathOverflow version of this question here.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.